UPAYA MENINGKATKAN MOTIVASI BERPRESTASI DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) DALAM PEMBELAJARAN MATEMATIKA DI KELAS VII-H SMPN 4 MADIUN - Erna Yulianawati; Rudi Santoso Yohanes (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2017)
This research aims is to increase the need of achievement together with the learning outcome for the students of the first grade of SMPN 4 Madiun using cooperative team game tournaments. Moreover, the use of Classroom Action Research (CAR) is indispensible. This research is done by applying  2 cycles as well. The subject of this research is the students of VII-H, in SMPN 4 Madiun, in the school year of 2015/2016. Moreover, the students who get involved in this research consists of 22 students. The data analysis shows that:The pecentage of minimal students in the high motivation achievement category of pre-action research cIass is 18,18%, the first cycle is 22,73% and the second cycle is 63,64%. The completion rate score due to Pre-CAR: 18,18%, cycle I: 22,73 %, and cycle II: 68,18%. The average score during the learning activity in cycle I is 3,06 which is classified as “good”. While, in cycle II the average score during the learning activity is 3,57. Which is classified as “good”. Teams Games Tournaments is considered as the effective way in ascending the need to achievement together with the students learning outcome. Key Word: Need to Achievement, Learning Outcome, Cooperative Learning, Teams Games Tournaments.